BMI and mortality among older adults in Belgium: the roles of age, sex, and frailty - Arne Noppe; Johan Van der Heyden; Hilde Baeyens; Ingrid Pelgrims; Sabine Drieskens; Anja Declercq; Brecht Devleesschauwer (Archives of Public Health, 2026)
Abstract Background Ageing populations and increasing prevalence of overweight are two of the main healthcare challenges worldwide. In 2023–2024, 49.7% of the Belgian population had overweight (BMI $$\ge$$ 25) and 3.1% of the population aged 65 years and above had underweight (BMI < 18.5). The health risks associated with high or low BMI and old age separately are well known. In addition, frailty is a key risk factor among older adults which is often associated with both mortality and BMI. Despite recent advances, there is an ongoing debate about how BMI relates to mortality risk among older and frail adults. This study assesses the BMI-mortality relationship and how it is affected by age, sex, and frailty status in the Belgian adult population. Methods Data were used from three waves of the Belgian Health Interview Survey (BHIS) linked with mortality follow-up data. Mortality risk was estimated in a representative sample of the Belgian population as a continuous hazard ratio in function of BMI. Stratification by age group (18–64, 65–84, 85 +), sex (male, female), and frailty status (robust/pre-frail, frail), allowed assessment of how the BMI-mortality relationship differed across these characteristics. Results Two effects were observed among older adults. First, the BMI range associated with the lowest risk for all-cause mortality shifts toward higher BMI values with increasing age. Second, the hazard ratio increase associated with higher BMI diminishes with older age, while the risk associated with lower BMI remains increased. These effects were observed in all populations. However, the effect sizes were larger among the female and the frail populations. Conclusion Our results suggest a protective effect associated with higher BMI in the Belgian population aged 65 and older, which is more pronounced over the age of 85. Furthermore, observed differences between men and women, and robust/pre-frail and frail adults suggest multiple characteristics should be taken into account for more accurate, stratified BMI categories. It is clear the definition of healthy BMI should be reevaluated among older adults to minimize mortality risk.